A Citrulline‐Based Translational Population System Toxicology Model for Gastrointestinal‐Related Adverse Events Associated With Anticancer Treatments. (12th November 2019) - Yoneyama, Tomoki; Abdul‐Hadi, Kojo; Brown, Adam; Guan, Emily; Wagoner, Matt; Zhu, Andy Z.X.
Abstract : Gastrointestinal (GI)‐related adverse events (AEs) are commonly observed in the clinic during cancer treatments. Citrulline is a potentially translatable biomarker of GI AEs. In this study, irinotecan‐induced citrulline changes were studied for a range of doses and schedules in rats. A translational system toxicology model for GI AEs using citrulline was then developed based on new experimental data and parameters from a literature intestinal cell dynamic model. With the addition of feedback‐development and tolerance‐development mechanisms, the model well captured the plasma citrulline profiles after irinotecan treatment in rats. Subsequently, the model was translated to humans and predicted the observed GI AE dynamics in humans including dose‐scheduling effect using the cytotoxic and feedback parameters estimated in rats with slight calibrations. This translational toxicology model could be used for other antineoplastic drugs to simulate various clinical dosing scenarios before human studies and mitigate potential GI AEs.